2008
DOI: 10.1590/s0100-06832008000100036
|View full text |Cite
|
Sign up to set email alerts
|

Frações de nitrogênio em Luvissolo sob sistemas agroflorestais e convencional no semi-árido cearense

Abstract: Os sistemas agroflorestais têm sido amplamente promovidos como sistemas de produção agrícola sustentáveis, principalmente para regiões subdesenvolvidas, onde o uso de insumos externos é inviável. Este trabalho objetivou avaliar o impacto de quatro sistemas agroflorestais e um sistema convencional sobre os teores de N total, mineral e em diferentes frações orgânicas, após cinco anos de uso de um Luvissolo na região semi-árida cearense, em experimento instalado na Embrapa Caprinos, em Sobral (CE). Os sistemas te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 26 publications
0
12
0
3
Order By: Relevance
“…Respectively, the TN levels in the TR, AGP and SIL systems were 56, 13.9 and 15.8 % of the levels under NV at 0-6 cm; 42.2, 16.8 and 14.9 % of the NV levels at 6-12 cm; and 30.8, 16.2 and 4.4 % of the NV levels at 12-20 cm (Figure 6). Maia et al (2008) found TN levels of 5.46 and 3.02 g kg -1 in the 0-6 and 6-12-cm layers in the same experimental area, respectively, and attributed these high values to the higher soil clay content and the effect of organic matter on the topsoil, thus demonstrating the relationship between the organic and mineral soil fractions. Significant TN losses were observed in the TR agricultural system over time; the TN levels were 83.3 and 79.8 % lower in 2011 than they were in 2002.…”
Section: Total Soil Nitrogen Levels and Stocksmentioning
confidence: 69%
See 4 more Smart Citations
“…Respectively, the TN levels in the TR, AGP and SIL systems were 56, 13.9 and 15.8 % of the levels under NV at 0-6 cm; 42.2, 16.8 and 14.9 % of the NV levels at 6-12 cm; and 30.8, 16.2 and 4.4 % of the NV levels at 12-20 cm (Figure 6). Maia et al (2008) found TN levels of 5.46 and 3.02 g kg -1 in the 0-6 and 6-12-cm layers in the same experimental area, respectively, and attributed these high values to the higher soil clay content and the effect of organic matter on the topsoil, thus demonstrating the relationship between the organic and mineral soil fractions. Significant TN losses were observed in the TR agricultural system over time; the TN levels were 83.3 and 79.8 % lower in 2011 than they were in 2002.…”
Section: Total Soil Nitrogen Levels and Stocksmentioning
confidence: 69%
“…These results clearly indicate that any tillage, regardless of intensity, promotes reduced soil TOC levels (Figure 2) (Maia et al, 2007(Maia et al, , 2008Veum et al, 2011;Novara et al, 2012); this is most likely due to an increased rate of organic matter decomposition (Novara et al, 2012). The landform can aggravate these disturbances and maximize the effects of the different studied management systems.…”
Section: Soil Total Organic Carbon Levels and Stocksmentioning
confidence: 85%
See 3 more Smart Citations